Development of metallized three-directional fibre Bragg grating strain sensor. (October 2020) - Chen, D.M.; Dai, X.N.; Tang, Z.B.
Abstract: The theory and application of fiber Bragg grating sensors are studied in this paper. The three-directional metallized fiber Bragg grating strain sensor with temperature compensation has been developed. The Metallization Technology of fiber grating is studied. The Metallization Technology Scheme of fiber grating is discussed in detail. The electroless composite nickel-plating process and the formula of nickel-plating process are given. A metal fiber grating strain sensor with temperature compensation is developed. The metal fiber grating sensor is fixed to the substrate by laser welding, and a one-way metal fiber grating strain sensor with temperature compensation is formed. Three unidirectional metallized fiber Bragg grating strain sensors are connected with the developed common welding blocks to form a three-directional strain flower. Comparing with resistance strain rosette stress test and its application in ship structure stress monitoring, the fiber grating strain sensor developed in this paper fully meets the requirements of large-scale structure long-term strain monitoring.